Early Predictors in the Onset of Type 2 Diabetes at Different Fasting Blood Glucose Levels - Xie X (Dove Medical Press, 2021)
Xiaomin Xie,* Guirong Bai,* Huili Liu, Li Zhang, YanTing He, Dan Qiang, Xiaoyan Zou Department of Endocrinology, The First People’s Hospital of Yinchuan, Yinchuan, 750001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaomin XieDepartment of Endocrinology, The First People’s Hospital of Yinchuan, 2 Liqun Street, Xingqing District, Yinchuan, 750001, Ningxia, People’s Republic of ChinaTel +86 13895189599Email xxm2324@126.comPurpose: This study investigates the possible roles and potential prediction ability of metabolic parameters in the early development of T2D by detecting their serum levels at different fasting blood glucose (FBG) levels.Methods: The subjects were included and divided into normal glucose tolerance (NGT), prediabetes (PD), and T2Dsubgroups. Apart from detecting the levels of routine biochemical parameters, fasting serum insulin (FINS), 25(OH)D, thioredoxin-interacting protein (TXNIP), thioredoxin (TRX), and NOD-like receptor family, pyrin domain-containing 3 (NLRP3) were detected. β-cell dysfunction (HOMA-β) and insulin resistance (HOMA-IR) were assessed by homeostasis model assessment. Both univariate and multivariate logistic regression analyses were used to estimate the risk of metabolic parameters, and their optimal cut-off values were obtained in the receiver operating characteristic (ROC) curve analysis and the Youden index.Results: Among the 207 subjects, aged from 20 to 60 years (44.62+12.92) contain 118 males and 89 females. There was a significantly lower trend of TRX, HOMA-β, and 25(OH)D following the higher FBG level among these three subgroups, while a significantly higher trend of all the other metabolic parameters. The multivariate analysis showed that subjects with higher values of TRX, HOMA-β, and 25(OH)D had a significantly lower risk for patients to be diagnosed as PD (aOR: 0.945, 0.961, and 0.543) and T2D (aOR: 0.912, 0.947, 0.434). Under the reliable 95% CI, TXNIP with a cut-off value of 119.27 showed the highest AUC value, sensitivity, and specificity (AUC: 0.981, 95% CI: 0.8524– 0.9839, 91.49%, and 83.33%) to diagnose PD. FINS with a cut-off value of 28.1 also showed the highest ones (AUC=0.9872, 95% CI: 0.9753– 0.9992, 100%, and 92.91%) to diagnose T2D.Conclusion: Early prediction of T2D is vital for timely intervention. Based on the FBG ≥ 100.8 mg/dl, the results provide evidence that 25(OH)D might be the protective factor in the early development of T2D. Besides, TXNIP and FINS might be the predictor for PD and T2D, respectively.Keywords: prediabetes, PD, type 2 diabetes, T2D, 25-hydroxyvitamin D, 25(OH)D, thioredoxin-interacting protein, TXNIP, β-cell dysfunction, insulin resistance